Meningkatkan Aktivitas, Motivasi Dan Hasil Belajar Matematika Menggunakan Model Peta - Nurmaida, Nurmaida; Aslamiah, Aslamiah (GLOBAL SCIENTS PUBLISHER, 2025)
The problem in this research is the low level of activity, motivation and student learning outcomes. This is caused by one-way learning, lack of student activity during the learning process, not using varied learning models and media, and monotonous learning. Efforts to overcome this are by using the PETA model which consists of the Problem Based Learning Model, Example Non Example Model, Teams Games Tournament Model. The aim of this research is to describe teacher activities, analyze increased student activity, student learning motivation, and learning outcomes. This research used PTK which was carried out in 4 meetings. The research subjects were 9 grade IV students at SDN 2 Pangeran, in the second semester of the 2023/2024 academic year. This research uses a qualitative approach. Data was obtained through observing teacher activities, student activities, student learning motivation, as well as learning outcomes obtained through group and individual written tests.